Variability in Platelet-Rich Plasma Preparations Used in Regenerative Medicine: A Comparative Analysis - Raghvendra Vikram Tey; Pallavi Haldankar; Vivek R. Joshi; Rishi Raj; Ravindra Maradi (Stem Cells International)
Background. Platelet-rich plasma (PRP) and its derivatives are used in several aesthetic, dental, and musculoskeletal procedures. Their efficacy is primarily due to the release of various growth factors (GF), interleukins, cytokines, and white blood cells. However, the PRP preparation methods are highly variable, and studies lack consistency in reporting complete procedures to prepare PRP and characterize PRP and its derivatives. Also, all the tissue-specific (in vivo and in vitro) interactions and functional properties of the various derivatives/factors of the PRP have not been taken into consideration by any study so far. This creates a potential space for further standardization of the PRP preparation methods and customization of PRP/PRP derivatives targeted at tissue-specific/pathology specific requirements that would enable efficacious and widely acceptable usage of PRP as main therapy, rather than being used as adjuvant therapy. The main objective of our study was to investigate the variability in PRP preparation methods and to analyze their efficacy and reliability. Method. This study considered articles published in the last 5 years, highlighting the variability in their PRP preparation methods and characterization of PRP. Following the PRISMA protocol, we selected 13 articles for the study. The selected articles were assessed using NHLBI quality assessment tool. Results. We noted differences in (1) approaches to producing PRP, (2) extent of characterization of PRP, (3) small scale and large-scale preparation methods, (4) in vitro and in vivo studies. Conclusion. We identified two studies describing the procedures which are simple, reproducible, economical, provide a good yield of platelets, and therefore can be considered methods for further tissue-specific and pathology-specific standardizations of PRP and its derivatives. We recommend further randomized studies to understand the full therapeutic potential of the constituents of PRP and its derivatives.